Biallelic mutations in LAMA5 disrupts a skeletal noncanonical focal adhesion pathway and produces a distinct bent bone dysplasia. - Barad, Maya; Csukasi, Fabiana; Bosakova, Michaela; Martin, Jorge H; Zhang, Wenjuan; Paige Taylor, S; Lachman, Ralph S; Zieba, Jennifer; Bamshad, Michael; Nickerson, Deborah; Chong, Jessica X; Cohn, Daniel H; et al. (EBioMedicine, 2020)
BACKGROUND: Beyond its structural role in the skeleton, the extracellular matrix (ECM), particularly basement membrane proteins, facilitates communication with intracellular signaling pathways and cell to cell interactions to control differentiation, proliferation, migration and survival. Alterations in extracellular proteins cause a number of skeletal disorders, yet the consequences of an abnormal ECM on cellular communication remains less well understood METHODS: Clinical and radiographic examinations defined the phenotype in this unappreciated bent bone skeletal disorder. Exome analysis identified the genetic alteration, confirmed by Sanger sequencing. Quantitative PCR, western blot analyses, immunohistochemistry, luciferase assay for WNT signaling were employed to determine RNA, proteins levels and localization, and dissect out the underlying cell signaling abnormalities.  Migration and wound healing assays examined cell migration properties. FINDINGS: This bent bone dysplasia resulted from biallelic mutations in LAMA5, the gene encoding the alpha-5 laminin basement membrane protein. This finding uncovered a mechanism of disease driven by ECM-cell interactions between alpha-5-containing laminins, and integrin-mediated focal adhesion signaling, particularly in cartilage. Loss of LAMA5 altered β1 integrin signaling through the non-canonical kinase PYK2 and the skeletal enriched SRC kinase, FYN. Loss of LAMA5 negatively impacted the actin cytoskeleton, vinculin localization, and WNT signaling. INTERPRETATION: This newly described mechanism revealed a LAMA5-β1 Integrin-PYK2-FYN focal adhesion complex that regulates skeletogenesis, impacted WNT signaling and, when dysregulated, produced a distinct skeletal disorder. FUNDING: Supported by NIH awards R01 AR066124, R01 DE019567, R01 HD070394, and U54HG006493, and Czech Republic grants INTER-ACTION LTAUSA19030, V18-08-00567 and GA19-20123S.

Dominant-negative SOX9 mutations in campomelic dysplasia. - Csukasi, Fabiana; Duran, Ivan; Zhang, Wenjuan; Martin, Jorge H; Barad, Maya; Bamshad, Michael; Weis, Mary Ann; Eyre, David; Krakow, Deborah; Cohn, Daniel H (Hum Mutat, 2019)
Campomelic dysplasia (CD) is an autosomal dominant, perinatal lethal skeletal dysplasia characterized by a small chest and short long bones with bowing of the lower extremities. CD is the result of heterozygosity for mutations in the gene encoding the chondrogenesis master regulator, SOX9. Loss-of-function mutations have been identified in most CD cases so it has been assumed that the disease results from haploinsufficiency for SOX9. Here, we identified distal truncating SOX9 mutations in four unrelated CD cases. The mutations all leave the dimerization and DNA-binding domains intact and cultured chondrocytes from three of the four cases synthesized truncated SOX9. Relative to CD resulting from haploinsufficiency, there was decreased transactivation activity toward a major transcriptional target, COL2A1, consistent with the mutations exerting a dominant-negative effect. For one of the cases, the phenotypic consequence was a very severe form of CD, with a pronounced effect on vertebral and limb development. The data identify a novel molecular mechanism of disease in CD in which the truncated protein leads to a distinct and more significant effect on SOX9 function.

Expanding the genetic architecture and phenotypic spectrum in the skeletal ciliopathies. - Zhang, Wenjuan; Taylor, S Paige; Ennis, Hayley A; Forlenza, Kimberly N; Duran, Ivan; Li, Bing; Sanchez, Jorge A Ortiz; Nevarez, Lisette; Nickerson, Deborah A; Bamshad, Michael; Lachman, Ralph S; Krakow, Deborah; et al. (Hum Mutat, 2018)
Defects in the biosynthesis and/or function of primary cilia cause a spectrum of disorders collectively referred to as ciliopathies. A subset of these disorders is distinguished by profound abnormalities of the skeleton that include a long narrow chest with markedly short ribs, extremely short limbs, and polydactyly. These include the perinatal lethal short-rib polydactyly syndromes (SRPS) and the less severe asphyxiating thoracic dystrophy (ATD), Ellis-van Creveld (EVC) syndrome, and cranioectodermal dysplasia (CED) phenotypes. To identify new genes and define the spectrum of mutations in the skeletal ciliopathies, we analyzed 152 unrelated families with SRPS, ATD, and EVC. Causal variants were discovered in 14 genes in 120 families, including one newly associated gene and two genes previously associated with other ciliopathies. These three genes encode components of three different ciliary complexes; FUZ, which encodes a planar cell polarity complex molecule; TRAF3IP1, which encodes an anterograde ciliary transport protein; and LBR, which encodes a nuclear membrane protein with sterol reductase activity. The results established the molecular basis of SRPS type IV, in which mutations were identified in four different ciliary genes. The data provide systematic insight regarding the genotypes associated with a large cohort of these genetically heterogeneous phenotypes and identified new ciliary components required for normal skeletal development.
Keywords: Ciliopathies; Cytoplasmic Dyneins; Genetic Association Studies; Genetic Markers; Genetic Variation; Genotype; Humans; Mutation; Phenotype; Proteins; Radiography; Skeleton; Whole Exome Sequencing

Mutations in IFT-A satellite core component genes and produce short rib polydactyly syndrome with distinctive campomelia. - Duran, Ivan; Taylor, S Paige; Zhang, Wenjuan; Martin, Jorge; Qureshi, Faisal; Jacques, Suzanne M; Wallerstein, Robert; Lachman, Ralph S; Nickerson, Deborah A; Bamshad, Michael; Cohn, Daniel H; Krakow, Deborah (Cilia, 2017)
BACKGROUND: Skeletal ciliopathies comprise a spectrum of ciliary malfunction disorders that have a profound effect on the skeleton. Most common among these disorders is short rib polydactyly syndrome (SRPS), a recessively inherited perinatal lethal condition characterized by a long narrow chest, markedly shortened long bones, polydactyly and, often, multi-organ system involvement. SRPS shows extensive locus heterogeneity with mutations in genes encoding proteins that participate in cilia formation and/or function. RESULTS: Herein we describe mutations in , a satellite member of the retrograde IFT-A complex, that produce a form of SRPS with unusual bending of the ribs and appendicular bones. These newly described mutations disrupted cilia formation, produced abnormalities in cartilage growth plate architecture thus contributing to altered endochondral ossification. We further show that the SRPS phenotype is similar to SRPS resulting from mutations in the gene encoding IFT121 (WDR35), a direct interactor with IFT43. CONCLUSIONS: This study defines a new -associated phenotype, identifying an additional locus for SRPS. The data demonstrate that IFT43 is essential for ciliogenesis and that the mutations disrupted the orderly proliferation and differentiation of growth plate chondrocytes, resulting in a severe effect on endochondral ossification and mineralization. Phenotypic similarities with SRPS cases resulting from mutations in the gene encoding the IFT43 direct interacting protein IFT121 suggests that similar mechanisms may be disrupted by defects in these two IFT-A satellite interactors.

A postnatal role for embryonic myosin revealed by MYH3 mutations that alter TGFβ signaling and cause autosomal dominant spondylocarpotarsal synostosis. - Zieba, Jennifer; Zhang, Wenjuan; Chong, Jessica X; Forlenza, Kimberly N; Martin, Jorge H; Heard, Kelly; Grange, Dorothy K; Butler, Merlin G; Kleefstra, Tjitske; Lachman, Ralph S; Nickerson, Deborah; Regnier, Michael; et al. (Sci Rep, 2017)
Spondylocarpotarsal synostosis (SCT) is a skeletal disorder characterized by progressive vertebral, carpal and tarsal fusions, and mild short stature. The majority of affected individuals have an autosomal recessive form of SCT and are homozygous or compound heterozygous for nonsense mutations in the gene that encodes the cytoskeletal protein filamin B (FLNB), but a subset do not have FLNB mutations. Exome sequence analysis of three SCT patients negative for FLNB mutations identified an autosomal dominant form of the disease due to heterozygosity for missense or nonsense mutations in MYH3, which encodes embryonic myosin. Cells transfected with the MYH3 missense mutations had reduced TGFβ signaling, revealing a regulatory role for embryonic myosin in the TGFβ signaling pathway. In wild-type mice, there was persistent postnatal expression of embryonic myosin in the small muscles joining the neural arches of the spine suggesting that loss of myosin function in these muscles contribute to the disease. Our findings demonstrate that dominant mutations in MYH3 underlie autosomal dominant SCT, identify a postnatal role for embryonic myosin and suggest that altered regulation of signal transduction in the muscles within the spine may lead to the development of vertebral fusions.
Keywords: Abnormalities, Multiple; Alleles; Bone Morphogenetic Proteins; Cytoskeletal Proteins; Female; Genes, Dominant; Genotype; Humans; Lumbar Vertebrae; Male; Musculoskeletal Diseases; Mutation; Myosins; Phenotype; Radiography; Scoliosis; Signal Transduction; Synostosis; Thoracic Vertebrae; Transforming Growth Factor beta; Whole Exome Sequencing

Destabilization of the IFT-B cilia core complex due to mutations in IFT81 causes a Spectrum of Short-Rib Polydactyly Syndrome. - Duran, Ivan; Taylor, S Paige; Zhang, Wenjuan; Martin, Jorge; Forlenza, Kimberly N; Spiro, Rhonda P; Nickerson, Deborah A; Bamshad, Michael; Cohn, Daniel H; Krakow, Deborah (Sci Rep, 2016)
Short-rib polydactyly syndromes (SRPS) and Asphyxiating thoracic dystrophy (ATD) or Jeune Syndrome are recessively inherited skeletal ciliopathies characterized by profound skeletal abnormalities and are frequently associated with polydactyly and multiorgan system involvement. SRPS are produced by mutations in genes that participate in the formation and function of primary cilia and usually result from disruption of retrograde intraflagellar (IFT) transport of the cilium. Herein we describe a new spectrum of SRPS caused by mutations in the gene IFT81, a key component of the IFT-B complex essential for anterograde transport. In mutant chondrocytes, the mutations led to low levels of IFT81 and mutant cells produced elongated cilia, had altered hedgehog signaling, had increased post-translation modification of tubulin, and showed evidence of destabilization of additional anterograde transport complex components. These findings demonstrate the importance of IFT81 in the skeleton, its role in the anterograde transport complex, and expand the number of loci associated with SRPS.

IFT52 mutations destabilize anterograde complex assembly, disrupt ciliogenesis and result in short rib polydactyly syndrome. - Zhang, Wenjuan; Taylor, S Paige; Nevarez, Lisette; Lachman, Ralph S; Nickerson, Deborah A; Bamshad, Michael; Krakow, Deborah; Cohn, Daniel H (Hum Mol Genet, 2016)
The short-rib polydactyly syndromes (SRPS) encompass a radiographically and genetically heterogeneous group of skeletal ciliopathies that are characterized by a long narrow chest, short extremities, and variable occurrence of polydactyly. Radiographic abnormalities include undermineralization of the calvarium, shortened and bowed appendicular bones, trident shaped acetabula and polydactyly. In a case of SRPS we identified compound heterozygosity for mutations in IFT52, which encodes a component of the anterograde intraflagellar transport complex. The IFT52 mutant cells synthesized a significantly reduced amount of IFT52 protein, leading to reduced synthesis of IFT74, IFT81, IFT88 and ARL13B, other key anterograde complex members. Ciliogenesis was also disrupted in the mutant cells, with a 60% reduction in the presence of cilia on mutant cells and loss of cilia length regulation for the cells with cilia. These data demonstrate that IFT52 is essential for anterograde complex integrity and for the biosynthesis and maintenance of cilia. The data identify a new locus for SRPS and show that IFT52 mutations result in a ciliopathy with primary effects on the skeleton.
Keywords: Carrier Proteins; Cilia; Ciliopathies; Cytoskeletal Proteins; Flagella; Humans; Intracellular Signaling Peptides and Proteins; Multiprotein Complexes; Muscle Proteins; Mutation; Short Rib-Polydactyly Syndrome; Skeleton; Tumor Suppressor Proteins